2021
DOI: 10.3390/ijgi10030186
|View full text |Cite
|
Sign up to set email alerts
|

Setting the Flow Accumulation Threshold Based on Environmental and Morphologic Features to Extract River Networks from Digital Elevation Models

Abstract: Determining the flow accumulation threshold (FAT) is a key task in the extraction of river networks from digital elevation models (DEMs). Several methods have been developed to extract river networks from Digital Elevation Models. However, few studies have considered the geomorphologic complexity in the FAT estimation and river network extraction. Recent studies estimated influencing factors’ impacts on the river length or drainage density without considering anthropogenic impacts and landscape patterns. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Subsequently, a stream network was generated by selecting a threshold on the flow accumulation raster. The turning point where river network density ceases to substantially increase with the threshold is often used as an optimal threshold [59]. However, to better detect small gullies, a relatively smaller threshold could be selected.…”
Section: Detecting Floor Elevation Of Erosion Gulliesmentioning
confidence: 99%
“…Subsequently, a stream network was generated by selecting a threshold on the flow accumulation raster. The turning point where river network density ceases to substantially increase with the threshold is often used as an optimal threshold [59]. However, to better detect small gullies, a relatively smaller threshold could be selected.…”
Section: Detecting Floor Elevation Of Erosion Gulliesmentioning
confidence: 99%
“…The mapping unit dataset with the OATMU for CES was defined as the OATMU group; the mapping unit dataset with the left ATMUs adjacent to the OATMU was defined left-OATMU group; the mapping unit dataset with the right ATMU adjacent to the OATMU was defined as the right-OATMU group; and the administrative village dataset within the Qiantang River Basin was defined as the administrative village group. By comparing the mean area, area quartile distance, and area maximum interval of the 3 ATMU groups and the administrative village group [26], the group with the minimum percent error of all three is the OATMU group for CES, and the corresponding ATMU is the OATMU for CES in the river basin. Validation was conducted using descriptive statistics and box plots in IBM SPSS Statistics 26 software.…”
Section: Validation Of the Oatmu For Cesmentioning
confidence: 99%
“…Therefore, with the establishment of appropriate units, CES can be accurately quantified [25]. Several studies in environmental hydraulics have used multiple catchment area thresholds for selecting the optimal area thresholds to obtain relatively homogeneous and refined mapping units [20,22,26]. To enhance mapping precision alongside computational efficiency, this study introduced the concept of area threshold, offering both a theoretical framework and a practical approach for accurately determining the appropriate area of mapping units.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the change in river network density becomes more gentle. Therefore, the river network image generated by the threshold at the in ection point is selected for comparison and veri cation with the restored river network image of the Ming Dynasty through graphic superposition (Figure 4) [20] . It is found that the river network image generated when the threshold is set to 100,000 is relatively close to the restored river network image of the Ming Dynasty, and at the same time, it is basically consistent with the main stream image of the restored Ming Dynasty river network.…”
Section: Research Aimmentioning
confidence: 99%